Detection of Wolbachia bacterium in Iranian strain of Trichogramma brassicae (Hym., Trichogrammatidae) - S. Farrokhi; M. E. Huigens; R. Zare; P. Verbaarschot (نامه انجمن حشره‌شناسی ایران, 2013)
Wolbachia (Î±-proteobacteria) strains are intracellular endosymbiont bacteria found in reproductive tissues of many arthropod species. In Trichogramma wasps, thelytokous parthenogenesis is mostly induced by this bacterium which inherited transovarially. In this study, the Wolbachia infection was detected based on the PCR method and wsp gene cloning in 49.5, 3.6 and 2.5% of Baboulsar, Chamestan and Nour populations of Trichogramma brassicae Bezdenko collected from Mazandaran province. The Baboulsar bacterium strain is submitted to GenBank (FJ441291) under the name wBaT.bra. The phylogenetic tree based on wsp sequences of Wolbachia strains in Trichogramma wasps indicates that the Iranian strains, wBaT.bra and Uro3 belonged to the same group (Sib group). With regard to the high rate infection in Baboulsar population of T. brassicae as a dominant species in Iran, it will be possible to assess the potential advantages of its asexual line in biological control projects.